The compressive and split tensile strength of nylon cable tie fibre-reinforced concrete - Izzul Azrai Nokman, 1992-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia